(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article is devoted to the history of Turkish state management system in the period since the establishment of Seljuk Empire to the beginning of Selim III reforms. This period is considered the beginning of the formation of the Turkish state, in which was based on state system in the Seljuk Empire. After this system was developed in the Ottoman Empire. We study the process of formation, development and decline of public administration in the Seljuk Empire, Ottoman state, administrative reforms of Orhan I, Mehmet II of, Suleyman the Magnificent, the evolution of the divan institute, the formation and development of the millet system of the Ottoman bureaucracy, the role of advisory councils in the management system. We analyze the system of province organization. It pays considerable attention to the formation and development of land tenure and taxation system in the Seljuk state and the Ottoman Empire, the evolution timar system of land tenure and the factors that led to the crisis of the system. The article has been used a retrospective approach to the study of the evolution of public administration development, land tenure and taxation in the Seljuk Empire and the Ottoman Empire. Key words: Turkey, the Seljuk state, the Ottoman Empire, the state, administration.